(untitled) (Superficies y Vacío, 2025)
This work aimed to synthesize and characterize CeO2:Eu2O3 ceramic powders with molar concentrations (Ce:Eu = 100:0, 98:2, 95:5, 92:8, 90:10, and 70:30). The gels were heat treated at 700 °C for 24 hours to induce crystallization of the ceramic powders. The materials were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), spectroscopy infrared spectroscopy (IR), Raman spectroscopy, scanning electron microscopy (SEM), photoluminescence (PL), and cathodoluminescence (CL). The results reveal that all ceramic powders presented a cubic (fluorite) structure with modifications in the lattice parameters as the Eu3+ concentrations changed. Furthermore, the Eu2O3 diffraction pattern allowed the complete identification of the crystal planes. The crystallite sizes were 64, 22, 30, 38, 40, and 50 nm for the Ce:Eu3+ ceramic powders at 100:0, 98:2, 95:5, 92:8, 90:10, and 70:30, respectively. XPS results showed a Ce3+/Ce4+ ratio of 0.27%. The IR spectrograms show the M-O bands attributable to CeO2 at 460, 560, 860, and 1200 cm-1. The results of the Raman spectra show three main bands at 260, 468, and 600 cm-1, which are associated with the F2g vibration mode of octahedral local symmetry found around the CeO2 lattice and the defect-induced mode related to the presence of oxygen vacancies due to the existence of Ce4+ ions. The particles exhibited morphological changes due to the change from the doped phase to the solid solution. The higher the concentration of Eu3+, the greater its agglomeration and size. The ceramic powders showed luminescent properties exhibiting emissions mainly by the 5D0-7D2 transition of Eu3+ and the 30 mol% sample showed higher luminescent intensity in cathodoluminescence.